The effect of 3% binahong leaf extract gel on the wound healing process of post tooth extraction - Olivia Avriyanti Hanafiah; Diana Sofia Hanafiah; Rahmi Syaflida (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: One of the common frequently performed procedures in dentistry is tooth extraction. After tooth extraction, a series of biological events occurs in the alveolar socket that ultimately results in healing of the socket. Binahong (Anredera cordifolia) is an herbaceous plant that contains active compounds that may accelerate the wound healing process. Purpose: The aim of this study is to investigate the effect of 3% binahong leaf extract gel on the healing process of the postextraction wound. Methods: 3% binahong leaf extract gel was prepared with the composition of 1 g carbopol, 1 g hydroxypropilmethylcellulose (HPMC), 4 g glycerin, 3 g triethanolamine (TEA), 0.04 g Nipagin, 0.04 g Nipasol, 1.2 g binahong leaf extract and Aq ad 40 g. A total of 18 people were subjected to tooth extraction and were then divided into two groups, with nine people in the binahong group and nine in the control group. Following that, residual socket volume (RSV) was examined on days 3, 7 and 14 after the extraction in both the binahong and control groups. The RSV value was obtained by calculating the mesiodistal x bucolingual width x the depth probing and measured using a calliper and probe. Repeated analysis of variance (ANOVA) and Friedman test followed by Wilcoxon and dependent t-test (p<0.05) were used to analyse data. Results: Significant difference in the mean RSV between the control and binahong groups was observed on days 3, 7 and 14 post tooth extraction. The RSV value in the binahong group was lower when compared to the control group (p <0.05). Conclusion: 3% binahong leaf extract gel can accelerate the process of healing socket wounds.